Tumor-induced Osteomalacia with Proximal Tubulopathy: A Case Report - Satjanon, Chamanant; Kitpermkiat, Rungthiwa (Journal of the Nephrology Society of Thailand, 2024)
Tumor-induced osteomalacia (TIO) is a rare paraneoplastic syndrome that poses diagnostic challenges. Most patients present with symptoms such as bone pain, fractures, or muscle weakness, which are caused by the tumor’s production of fibroblast growth factor-23 (FGF-23). This phosphaturic hormone decreases the expression of type 2 sodium-phosphate cotransporters (NaPi-2a and NaPi-2c) in the kidney’s proximal tubule, leading to hypophosphatemia due to increased phosphate excretion. Additionally, FGF-23 inhibits the enzyme 1α-hydroxylase (CYP27B1), which converts 25(OH)D to the active form of vitamin D, 1,25(OH)2D, while stimulating the enzyme 24-hydroxylase (CYP24A1), which increases the breakdown of 1,25(OH)2D. This reduction in active vitamin D contributes to the development of osteomalacia. Diagnosing TIO is often delayed due to the small size of the tumor, which is difficult to locate, and the non-specific symptoms. This article reports the case of a 58-year-old man who experienced bilateral thigh pain for three years. Initially diagnosed with osteoporosis, he was treated with pain medication, anti-resorptive therapy, and physical therapy. However, eight months before admission, his thigh pain worsened, and he had difficulty walking. Laboratory tests revealed renal phosphate wasting, hypophosphatemia, and elevated levels of intact FGF-23. Additionally, proteinuria, glucosuria, and elevated urine beta-2 microglobulin indicated proximal tubulopathy. A 99mTc-Hynic-TOC scan with SPECT/CT revealed increased uptake in the right medial thigh. He was diagnosed with TIO and Fanconi syndrome.